Perbandingan Efektivitas Model Pembelajaran Behavioristik, Kognitivistik, Dan Konstruktivistik - Gracesya Togatorop; Agus Lestari (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to compare the effectiveness of behavioristic, cognitivistic, and constructivistic learning models through a Systematic Literature Review (SLR) following the PRISMA protocol, analyzing 28 high-quality articles from 2015-2025 sourced from Scopus, Web of Science, Google Scholar, and ERIC. Synthesis results indicate that the constructivistic model is most effective in enhancing critical thinking skills, collaboration, and long-term retention (average effect size 0.75), followed by cognitivistic for deep information processing (0.65), and behavioristic for basic skill mastery (0.55), with key moderators including student age, subject matter, and technological support. The SLR addresses a research gap by providing a systematic empirical comparison previously fragmented in the literature, supporting the development of an integrative hybrid model aligned with Vygotsky's Zone of Proximal Development (ZPD), Ausubel's meaningful learning, and Skinner's operant conditioning theories, particularly relevant for Indonesia's Merdeka Curriculum in multicultural contexts like Jambi. Practical implications include recommendations for teachers to adopt hybrid approaches, MMAT-based training, and government policies to optimize 21st-century learning outcomes.​ Keywords: behavioristic learning model, cognitivistic, constructivistic, effectiveness, systematic literature review, hybrid learning Abstrak Penelitian ini bertujuan membandingkan efektivitas model pembelajaran behavioristik, kognitivistik, dan konstruktivistik melalui Systematic Literature Review (SLR) berbasis protokol PRISMA dari 28 artikel berkualitas tinggi periode 2015-2025 di database Scopus, Web of Science, Google Scholar, dan ERIC. Hasil sintesis menunjukkan model konstruktivistik paling efektif dalam meningkatkan keterampilan berpikir kritis, kolaborasi, dan retensi jangka panjang (effect size rata-rata 0.75), diikuti kognitivistik untuk pemrosesan informasi mendalam (0.65), serta behavioristik untuk penguasaan keterampilan dasar (0.55), dengan moderator utama berupa usia siswa, mata pelajaran, dan teknologi pendukung.​ SLR ini mengisi research gap dengan komparasi empiris sistematis yang sebelumnya fragmentaris, mendukung pengembangan model hybrid integratif sesuai teori Vygotsky (ZPD), Ausubel (meaningful learning), dan Skinner (operant conditioning), relevan untuk Kurikulum Merdeka di konteks multikultural Indonesia seperti Jambi. Implikasi praktis mencakup rekomendasi bagi guru untuk adopsi hybrid, pelatihan berbasis MMAT, dan kebijakan pemerintah guna optimalisasi prestasi belajar abad-21.​ Kata kunci: model pembelajaran behavioristik, kognitivistik, konstruktivistik, efektivitas, systematic literature review, pembelajaran hybrid